Acute pre- and post-competitive soccer match-play changes in neuromuscular factors, physical performance, and muscle response in youth male players - Martin-Garetxana, I.; Hughes, J.; De Ste Croix, M.; Larruskain, J.; Lekue, J. A.; Ayala, F. (Science and Medicine in Football, 2024)
There is a paucity of literature analyzing the impact of fatigue from actual competitive soccer match-play on measures of neuromuscular function and muscle damage markers in youth players. Aims The main purpose was to analyze the acute pre- and post-competitive soccer match-play changes in measures of landing mechanics, stretch-shortening cycle capability, physical performance, muscle damage, and match intensity. A secondary purpose was to explore whether the players` maturity status and chronological age were associated with post-soccer match-play responses. Methods Thirty-two male youth outfield soccer players from two chronological competition age groups (U14 and U16) were assessed pre-and post-competitive soccer match-play for 2D dynamic knee valgus at landing (DKV), leg stiffness, reactive strength index, 20 m sprint time, CMJ-Abalakov jump height, creatine kinase and urea activity and visual analogue scale for muscle soreness (VAS). Players` maturity status was also estimated using a previously validated regression equation. Results There were statistically significant (p < 0.05) post-competitive soccer match-play impairments in all measures of stretch-shortening cycle capability and muscle damage markers assessed irrespective of the age group. Likewise, significant post-match play alterations in landing mechanics (DKV of the dominant leg) and physical performance (sprint time and jump height) scores were documented for the U14 players. Significant interactions between maturity and landing mechanics and VAS responses to competitive soccer match-play were also found whereby more mature players demonstrated larger post-match changes. Conclusion The findings of this study suggest the existence of a negative influence of competitive match-play on neuromuscular function and muscle damage in youth soccer.